Pengaruh Akuntabilitas, Value For Money, dan Transparansi Anggaran Terhadap Pengelolaan Keuangan pada Organisasi Perangkat Daerah (OPD) di Kota Palembang - Wahyuningsih, Wahyuningsih; AR, Sopiyan; Dwitayanti, Yevi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of accountability, value for money, and budget transparency on financial management in Regional Apparatus Organizations (OPD) of Palembang City. The study was conducted in 32 OPD involving 96 respondents consisting of treasurers, heads of financial sub-divisions, and financial staff directly involved in regional financial management. Primary data were collected through questionnaires using a purposive sampling technique. Data analysis was carried out using descriptive statistics, data quality tests including validity and reliability tests, classical assumption tests consisting of normality, multicollinearity, and heteroscedasticity tests, as well as multiple linear regression analysis. Hypothesis testing was conducted through the coefficient of determination (R²), partial test (t-test), and simultaneous test (F-test) using SPSS version 26. The results indicate that accountability, value for money, and budget transparency have a positive and significant effect on financial management individually. Simultaneously, these three variables also have a positive and significant effect on financial management in OPDs of Palembang City. These findings suggest that strengthening accountability, implementing value for money principles, and enhancing budget transparency can improve the effectiveness, efficiency, and accountability of regional financial management.